The Relationship of Asean Country Identity Recognition to Students' Curiosity in Pandan Malaysia Learning Studio - Sembiring, Intan Sahpitri Br; Amelia, Chairunnisa; Nasution, Ismail Saleh (Universitas Pahlawan Tuanku Tambusai, 2026)
Education plays an important role in preserving cultural values and customs passed down from generation to generation while continuously adapting to societal changes. In the context of regional development, mastering ASEAN identity is essential for students to understand ASEAN member countries, their characteristics, and shared values. Low levels of curiosity among students can be addressed through the use of interactive and engaging learning media. This study aimed to determine the relationship between recognition of ASEAN identity and students’ curiosity at the Pandan Learning Centre in Malaysia. The study employed a quantitative correlational research design involving students as research participants. Data were collected using questionnaires and analyzed using a correlation test. The results showed a significance value of Sig. (2-tailed) of 0.000, which is less than 0.05, indicating a statistically significant relationship between ASEAN identity recognition and students’ curiosity. Therefore, it can be concluded that a higher level of ASEAN identity recognition is associated with increased curiosity among students.